Pengaruh pengetahuan perpajakan, sosialisasi perpajakan, kesadaran pajak, dan sanksi pajak terhadap kepatuhan wajib pajak UMKM - Utami, Intan; Suwarti, Titiek; Masdjojo, Gregornius N (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
One way to maximize tax revenue is that the DGT applies a self-assessment system. Indicators that need to be improved by taxpayers, including MSME actors, are knowledge of taxation, including tax calculations related to their business activities, as well as knowledge of the tax consequences of tax violations. To examine how the influence of information, socialization, knowledge, and tax sanctions on taxpayer compliance in micro, small and medium enterprises (MSMEs) in Semarang City, is the aim of this research. Semarang City MSME taxpayers became participants in this study. The data collection method was carried out by distributing questionnaires (Likert scale). Regression analysis using the SPSS 22 application was used as a data analysis method. The results of this study indicate that tax knowledge, tax socialization, and tax awareness simultaneously have a positive effect on tax obligations. This shows that the greater the knowledge, socialization, and awareness of taxes, the greater the MSME tax compliance. While the sanction variable has no effect on taxation, taxpayer compliance. This means that in this study, the taxpayer believes that tax sanctions are only limited to regulations.